Cyproterone acetate reduced antler growth in surgically castrated fallow deer - Bartŏs, L; Schams, D; Kierdorf, U; Fischer, K; Bubenik, G A; Siler, J; Losos, S; Tománek, M; Lastovková, J (The Journal of endocrinology, 2000)
We studied the role of androgens in antler growth. In particular, we investigated whether the onset of antler regrowth is triggered by a short-term pulse of testosterone and if low levels of androgens are required for antler growth. The study was conducted on 12 surgically castrated fallow deer bucks (Dama dama) aged approximately 27 months. Six animals (CA group) were given the antiandrogen, cyproterone acetate (CA, 1000 mg/treatment); the others were given vehicle solution only (control). Before each CA treatment, blood was sampled and analysed for testosterone, androstenedione, IGF-1, cortisol, FSH, and LH. CA treatment and blood sampling were performed 2 days before castration, on the day of castration and afterwards at 2-day intervals until day 22. Subsequently, CA treatment and blood sampling continued at weekly intervals until day 270. All animals cast their antlers, followed by antler regrowth in all control bucks, but in only four of the six CA-treated castrates. Plasma testosterone concentrations were low in all animals (between 0.01 and 0.20 ng/ml), but were significantly (P<0001) greater in the controls. In both groups, a temporary increase in testosterone values was recorded around the time of antler regrowth, the peak being significantly (P<0.01) higher in the controls. Androstenedione showed a similar pattern as testosterone. Plasma IGF-1 concentrations increased sharply during the antler growth spurt and did not differ significantly between the two groups throughout the study period. Cortisol concentrations were greater in controls than in the CA group. However, no link with the antler cycle was apparent. FSH and LH concentrations were higher in the controls for most of the study. Antlers produced by the control bucks were significantly larger than those in the CA group (P<0.03). For antler length, testosterone, androstenedione and IGF-1, areas under the curve (AUC) were calculated over the period of antler growth. For the pooled deer (n=12) significant correlations existed between AUCs of antler length and testosterone, but not for antler length and IGF-1. Also, a trend for a positive correlation between AUCs of antler length and androstenedione was noted. It is concluded that a plasma androgen concentration at least above a minimal threshold level is a necessary prerequisite for normal antler regrowth in fallow deer, and that this androgen effect is not mediated via circulating IGF-1. The biological role of low levels of androgens may be to sensitize antler cells to the stimulating effect of IGF.
Keywords: Hydrocortisone; orchiektomie; Antlers; androstendion; insulinu podobný růstový faktor I; Male; Testosterone; Luteinizing Hormone; testosteron; plocha pod křivkou; Androgen Antagonists; antagonisté androgenů; Follicle Stimulating Hormone; Linear Models; Animals; Insulin-Like Growth Factor I; Area Under Curve; Androstenedione; Cyproterone Acetate; Deer; vysoká zvěř; cyproteronacetát; zvířata; luteinizační hormon; mužské pohlaví; parohy; folikuly stimulující hormon; hydrokortison; Orchiectomy; lineární modely